Preparing medical first responders for crises: a systematic literature review of disaster training programs and their effectiveness - Baetzner, Anke; Wespi, Rafael; Hill, Yannick; Gyllencreutz, Lina; Sauter, Thomas C.; Saveman, Britt-Inger; Mohr, Stefan; Regal, Georg; Wrzus, Cornelia; Frenkel, Marie Ottilie (Scandinavian journal of trauma, resuscitation and emergency medicine, 2022)
Adequate training and preparation of medical first responders (MFRs) are essential for an optimal performance in highly demanding situations like disasters (e.g., mass accidents, natural catastrophes). The training needs to be as effective as possible, because precise and effective behavior of MFRs under stress is central for ensuring patients’ survival and recovery. This systematic review offers an overview of scientifically evaluated training methods used to prepare MFRs for disasters. It identifies different effectiveness indicators and provides an additional analysis of how and to what extent the innovative training technologies virtual (VR) and mixed reality (MR) are included in disaster training research.